(untitled) (Estudos em Design, 2026)
Editores Cristina Portugal Rita Couto Avaliadores desta edição V. 34, n. 1 (2026) Adriana Gralow Adriana Miranda Adriana Sampaio Leite Alexandre Oliveira Aline Savi Álvaro Sousa Ana Beatriz Pereira de Andrade Ana Berwanger Ana Pazmino Andre Batistella Souza André Ribeiro de Oliveira Artur Mottin Bruno Serviliano Farias Carlo Franzato Carolina Vaitiekunas Pizarro Cassia Carrara Domiciano Cassia Furtado Chrystianne Ivanóski Cláudia Silva Cyntia Malaguti de Sousa Daniel Raposo Daniela Estaregue Alves Doris Kosminsky Edson Rufino Ekaterina Barcellos Everton da Silva Fabiane Fernandes Fábio Caparica de Luna Fausto Medola Felipe Viaro Fernando Fogliano Frederico Braida Gabriel Patrocinio Gisela Campos Guilherme Altmayer Gustavo Curcio Igor Ramos Luiza Falcão Soares Cunha Luiz Guilherme Oliveira Marques Marcio Guimarães Maria Do Carmo Gonçalves Curtis Olavo Neto Otniel Altamirano Patrícia Braga Patrícia dos Santos Rafaela Sarinho Rafaella Peres Ravi Passos Renata Cadena Renata Wanderley Rogério Camara Rosane Martins Sandra Maria Souza Sérgio Luciano da Silva Silvia Schnaider Tiago Silva Walter Correia Vera Damazio Verônica Freire